Effect of power training on function and body composition in older women with probable sarcopenia. A study protocol for a randomized controlled trial - Luis Polo-Ferrero; Susana Saez-Gutierrez; Arturo Dávila-Marcos; Fausto J. Barbero-Iglesias; María C. Sánchez-Sánchez; Ana Silvia Puente-Gonzalez; Roberto Mendez-Sanchez (PLoS ONE, 2025)
Background Sarcopenia is a clinical syndrome characterized by the loss of muscle mass and strength. Hormonal changes that occur early in women may influence protein synthesis and promote muscle atrophy, leading to probable sarcopenia, defined as a loss of muscle strength without an obvious decrease in muscle mass. Various types of exercise have already proven effective in treating sarcopenia. Power training (PT), a subtype of resistance training performed at high speed, has not yet been studied in this population group. Methods A randomized controlled trial will be conducted with three parallel groups: a PT group, a multicomponent training (MT) group, and a no-exercise group. The inclusion criteria will be women over 65 years of age who meet the diagnostic criteria for probable sarcopenia (Hand grip test less than 16 kg and Five Times Sit to Stand Test more than 15 s) according to the European Working Group on Sarcopenia in Older People (EWGSOP2). Two assessments will be conducted at the beginning and at the end of the 32 weeks of intervention, in which variables of body composition (muscle, fat and weight) and functionality (strength and physical performance) will be collected. There will be 3 sessions of 50 minutes per week in each intervention group. The masking strategy will be double-blind. The analysis of intergroup differences will be conducted using multivariate and univariate analysis of variance (MANOVA and ANOVA), as well as pairwise comparisons (Bonferroni corrections). Changes in the degree of sarcopenia and how many women eliminate the risk of sarcopenia (no probable sarcopenia) after the different interventions will be tested. Discussion The study aims to investigate the impact of PT in older women at risk of sarcopenia. The expected results are that PT will significantly improve functionality and body composition compared to other forms of exercise (MT) and no physical activity. The results may represent a significant advance in understanding and addressing sarcopenia before it becomes established, providing preventive treatment and new tools whose clinical applicability has been studied. Trial registration The clinical trial was prospectively registered at ClinicalTrials.gov Identifier: NCT05870046.